Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1590/0102-33062016abb0223
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of arbuscular mycorrhizal fungi in high altitude sites of the Patagonian Altoandina region in Nahuel Huapi National Park (Argentina)

Abstract: Knowledge of the occurrence and diversity of arbuscular mycorrhizal fungi (AMF) in National Parks is essential for the establishment of policies for conservation. Th e aim of this study was to characterize the AMF communities in the Patagonian Altoandina region in Nahuel Huapi National Park, Argentina. We surveyed AMF spores associated with the rhizospheres of 9 plant species in the Patagonian Steppe (PS), Challhuaco Hill (ChH), Catedral Hill (CH), and Tronador Hill (TH) regions and detected a total of 27 Glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…It is worth stressing such large variations in the AMF colonizing the same plant species in a relatively small and geographically uniform area with the same aridity index. This clearly shows that AMF communities are influenced not only by the host plant, but also by local environmental factors, besides aridity level (Coutinho et al, 2015; Velázquez et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…It is worth stressing such large variations in the AMF colonizing the same plant species in a relatively small and geographically uniform area with the same aridity index. This clearly shows that AMF communities are influenced not only by the host plant, but also by local environmental factors, besides aridity level (Coutinho et al, 2015; Velázquez et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…less the same species, with a predominance of Maytenus chubutensis and shrub species. It has previously been reported (Fernández et al, 2012;Fontenla et al, 1998Fontenla et al, , 2001Velázquez et al, 2016;Godoy and Marín, 2019) that AM plants are the most abundant in the native forest of North Patagonia, not only in forest where the dominant tree species had AM, such as those dominated by ECM native species, Nothofagus spp. In the mixed woodland analyzed here, the species with highest cover were associated with AM symbiosis.…”
Section: Tablementioning
confidence: 91%
“…AM fungi associate with 70–80% of land plants in all major biomes (8) and enhance the growth of host plants by enhancing the uptake of mineral nutrients, particularly phosphorus (41). Many pioneer species in early primary succession on volcanic slopes (14, 43) and at high elevations (11, 28, 30, 31, 42) form AM associations. It has been demonstrated that the fungi play a significant role in the establishment of pioneer vegetation; e.g ., M. sinensis and the legume pioneer Lespedeza cyrtobotrya are highly dependent on AM associations for their establishment in acidic soil (33).…”
mentioning
confidence: 99%